Hubungan Penggunaan Sosial Media Terhadap Kesejahteraan Mental Remaja: Perspektif Siswa Sekolah SMA di Jakarta Barat - Apriyani Daeli, Fanny (Dinasti Research, 2024)
This study aims to explore the correlation between social media usage and the mental well-being of teenagers in Senior High Schools (SMA) in West Jakarta. The research is grounded in psychological theories that link social media usage to adolescent mental well-being. The choice of SMA in West Jakarta is to investigate the extent of the impact of social media usage on the well-being of teenagers in that area. The research method involves the use of two quantitative measurement instruments: the Internet Addiction Test to measure smartphone technology usage in the context of social media, and the Depression Anxiety Stress Scales to measure the level of students' mental well-being. This study employs a quantitative method with nonparametric analysis using SPSS. Data were collected through a questionnaire technique with random sampling. The respondents consist of 150 SMA students in West Jakarta. The research findings show a correlation coefficient of 0.838**, indicating a very strong and positive correlation between social media usage and adolescent mental well-being, as well as a significant relationship between these two variables. These findings suggest that high social media usage has the potential to affect students' mental well-being. The implications of this research provide a deeper understanding of the importance of mental well-being and the impact of excessive social media usage, particularly among school-going adolescents. Furthermore, these findings encourage future education, parenting, and interventions related to the importance of mental health and the consequences of excessive social media usage among teenagers.